Persejajaran Unsur-unsur Autochton dalam Cerita Panji Angreni dengan Cerita PantunMundinglaya Dikusumah - Anung Tedjowirawan (Humaniora, 2004)
Panji Angreni is a popular Panji story while the others besides Mundignlaya Dikusumah poem story a well known Sunda poesm, besides Lutung Kesarung, Ciung Wanara, and Nyi Sumur Bandung. Lirk common poems, Mundinglaya Dikusumah story belongs to a series of sacred stories or legends and is connected with traditional ceremonies such as children circumcision or marriage. The connection between Panji story with Padjajaran King. Fact of that Prabu Surya Amiluhur as a figure Panji story, will be the King of Padjajaran in the future. Poerbatjaraka and Berf claimed that Panji stories have historical background Poerbatjaraka placed the figure, in the era of Kediri while Berg placed them during the region of Hayam Wuruk in Majapahit Kingdom by Hayam Wuruk King. Rases Anthropology Structure Analysis of Panji Angreni Story and Mundinglaya Dikusumah poem story explained that both of the stories contained autochton principles which include; a)Totemisme, b) Classification System, c) Myte, 4) Cross Caussine, e) Stamheros and f) Intitation.